2014
DOI: 10.1002/jat.3060
|View full text |Cite
|
Sign up to set email alerts
|

Development of haemostatic decontaminants for the treatment of wounds contaminated with chemical warfare agents. 2: Evaluation of in vitro topical decontamination efficacy using undamaged skin

Abstract: The risk of penetrating, traumatic injury occurring in a chemically contaminated environment cannot be discounted. Should a traumatic injury be contaminated with a chemical warfare (CW) agent, it is likely that standard haemostatic treatment options would be complicated by the need to decontaminate the wound milieu. Thus, there is a need to develop haemostatic products that can simultaneously arrest haemorrhage and decontaminate CW agents. The purpose of this study was to evaluate a number of candidate haemost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In vitro skin diffusion cells are a validated method for measuring percutaneous absorption of chemicals (Chilcott et al, ; OECD, ), including CW agents such as GD, HD and VX (Chilcott et al, ; Dalton et al, , ; Vallet et al, ; van Hooidonk et al, ). Human skin is the gold standard model for in vitro percutaneous absorption studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro skin diffusion cells are a validated method for measuring percutaneous absorption of chemicals (Chilcott et al, ; OECD, ), including CW agents such as GD, HD and VX (Chilcott et al, ; Dalton et al, , ; Vallet et al, ; van Hooidonk et al, ). Human skin is the gold standard model for in vitro percutaneous absorption studies.…”
Section: Discussionmentioning
confidence: 99%
“…Three haemostatic products identified from a previous study (Dalton et al, ) were included in the present study as test decontaminants: QuikClot Advanced Clotting Sponge Plus® (Z‐Medica Corporation, Wallingford, CT, USA); ProQR® (Biolife, Sarasota, FL, USA); and WoundStat™ (TraumaCure, Bethesda, MD, USA). The current in‐service decontaminant fuller's earth (Sigma Chemical Co., Dorset, UK), was included as a positive control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a product suitable for halting bleeding and decontaminating wounds or abraded skin would be of significant clinical benefit. Previous studies have demonstrated that WoundStat™, a granular haemostat, has comparable efficacy to in‐service military decontaminants (fuller's earth and M291) in the decontamination of both undamaged and damaged skin (Dalton et al ., , Lydon et al ., ). Additionally, WoundStat™ maintains its haemostatic capability in the presence of toxic chemicals, including SM, in vitro (Hall et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Previous in vitro studies have demonstrated that haemostatic products may retain the ability to clot blood in the presence of CWAs and that certain products (based on absorptive powders) are able to effectively decontaminate CWAs from normal and superficiallydamaged skin (11)(12)(13). One product, WoundStat™, was identified as being particularly effective in terms of its ability to decontaminate CWAs from undamaged or superficiallydamaged skin.…”
Section: Introductionmentioning
confidence: 99%